Sosialisasi Pentingnya NPWP Bagi UMKM Pada Usaha Ikan Bakar Laut Timor Dan Usaha Salon Hyra - Agustina Suni; Ratri Paramitalaksmi (Jurnal Pengabdian Kepada Masyarakat, 2023)
This study examines the significance of the taxpayer identification number (NPWP) for micro, small, and medium-sized enterprises (MSMEs) through case studies of two distinct industries: the salon industry and the Timor Sea grilled fish industry. A tax notification known as NPWP is necessary for all taxpayers, even MSMEs. In these two businesses, the lack of an NPWP has several detrimental effects, such as restricted financial access, transaction prohibitions, and legal restrictions. Financial surveillance and possible third-party cooperation are also impacted by this. In order to assist MSMEs in expanding and improving their enterprises, this study examines NPWP. In addition to being a tax requirement, having an NPWP is crucial for the growth of MSME enterprises